1998
DOI: 10.1016/s0735-1097(98)00212-5
|View full text |Cite
|
Sign up to set email alerts
|

Basis for detection of stenosis using venous administration of microbubbles during myocardial contrast echocardiography: bolus or continuous infusion?

Abstract: Both bolus injection and continuous infusion provide quantitative assessment of relative stenosis severity. Compared with bolus injection, continuous infusion also allows quantification of MBF and data acquisition without attenuation of any myocardial bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(93 citation statements)
references
References 9 publications
3
88
1
1
Order By: Relevance
“…These include the diagnosis of liver lesions [2], the assessment of microvascular damage after a myocardial infarction [3] and the detection of coronary disease [4]. Microbubbles are a pure blood pool contrast agent, because their size is of the same order as red blood cells and thus cannot leave the vascular bed and escape in the interstitium [5], [6]. Their size along with their unique acoustic properties allow for the imaging of perfusion in real time using diagnostic ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…These include the diagnosis of liver lesions [2], the assessment of microvascular damage after a myocardial infarction [3] and the detection of coronary disease [4]. Microbubbles are a pure blood pool contrast agent, because their size is of the same order as red blood cells and thus cannot leave the vascular bed and escape in the interstitium [5], [6]. Their size along with their unique acoustic properties allow for the imaging of perfusion in real time using diagnostic ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Following the administration of low-dose dipyridamole, images are acquired at one transmission per cardiac cycle, and a decrease in myocardial enhancement is observed on the endocardial surface in areas supplied by a stenotic coronary artery [37][38][39]. VoluMap analysis clearly demonstrates the reduced RMCI on the endocardial surface, providing images that are easily interpreted even by inexperienced users (Figure 9).…”
Section: Volumetric Imagingmentioning
confidence: 99%
“…MCE is based on the microvascular rheology of microbubbles that is similar to that of red blood cells. Wei et al [25] and Jayaweera et al [26] have shown that the magnitude of a myocardial perfusion defect in a clinical study following the administration of adenosine is related to the severity of coronary stenoses. A recent study has demonstrated that the sensitivity of myocardial contrast perfusion abnormalities is greater than that of wall motion abnormalities for the detection of coronary stenosis > 50% diameter, even at a low dose of dobutamine infusion [13].…”
Section: Mce During Dsementioning
confidence: 99%